Safety in the use of medicinal and phytotherapy plants during pregnancy (Research, Society and Development, 2022)
Introduction: Medicinal plants offer in their composition bioactive substances with prophylactic or therapeutic properties and phytotherapics are medicines obtained from this plant raw material. The period of physiological events that imply symptoms of changes in a physical, emotional and female aspect, accompanied by various symptoms, such as nausea, vomiting and heartburn. Therefore, as pregnant women, they seek alternatives to relieve plants from plants, including medicines and phytotherapics. Objective: To analyze the safety of the use of scientific plants and herbal medicines given pregnancy. Methodology: A literature review was carried out, in the SCIELO, LILACS and MEDLINE databases, on the topic. Result and discussion: Although medicinal herbs and herbal medicines are considered risks by the population, this is a dangerous practice when done without guidance, and can offer a high during an education. In this context, it is essential to pay extra attention to the guidelines and care with the use of these products, since most of them do not have scientific proof of safety or the need for their use in pregnancy. Conclusion: Data the need for more scientific studies to prove the safety of these products, maternal and fetal health.